Penilaian Kepuasaan User dalam Menggunakan APlikasi SIM ASN Menggunakan Metode Website Quality: Teknik Informasi - Kasuma, Hidayatul Rahman; Huda, Baenil; Hilabi, Shofa Sofiah (IAI Nasional Laa Roiba Bogor, 2024)
Implementation of the State Civil Apparatus Management Information System (SIM ASN) is a must. The ASN SIM is not only an administrative tool, but is a digital ecosystem that integrates all personnel application services. The problem that occurs in the ASN SIM application is that users find it difficult to complete the complete history requested by the ASN SIM in the personnel database to update employee data history. The aim of this study is to assess the impact of three factors on user satisfaction: application quality, user-friendliness, and interaction quality. The evaluation process is based on the Website Quality technique, which takes into account multiple aspects of website quality, such as as information content, security, usability, speed, and interface design. Respondents in this study were frequent users of the ASN SIM Application. Questionnaires were used to gather information about user opinions and experiences with the quality of the program. To characterize the degree of user satisfaction and the variables influencing it, data analysis was carried out using both statistical and qualitative methodologies. In order to enhance the user experience and efficacy of using the ASN SIM Application in the everyday work environment, it is intended that the research findings will offer comprehensive insight into the areas that require further development. This study adds to the body of knowledge about user satisfaction evaluation in the context of government apps and may serve as a model for future research on the subject.